Gingival Vitiligo: Report of a Case and Review of the Literature - Nipun Ashok; Anila Karunakaran; Prabath Singh; Jean Rodrigues; Navya Ashok; Bassel Tarakji; Azzeghaiby Saleh; Alzoghaibi Ibrahim (Case Reports in Dentistry)
Rarely cases have been reported regarding depigmented lesions of the oral cavity. On reviewing the literature, only few cases of gingival vitiligo or similar lesions have been reported till date. These lesions pose a cosmetic challenge. We present here a case of vitiligo affecting gingiva. Vitiligo has been defined as an acquired, slowly progressive loss of cutaneous pigment which occurs as irregular, sharply defined patches which may or may not be surrounded by macroscopic hyperpigmentation. Differential diagnosis, detailed clinical history, histopathology, immunohistochemistry, and pathogenesis of this condition are discussed.